RADIOGRAPHIC FEATURES OF INTERNAL STRUCTURE IN JAW LESIONS (Review article) - Norlaila Sarifah; Ria N.Firman; Farina Pramanik; Lusi Epsilawati (FKG Unlam, 2019)
Background: The internal structure of jaw lesions demonstrates different characteristics and distinctions. They may be varied in features such as the four variations of internal structure presented in ameloblastoma. Each type represents distinctive characteristics which depict the natures of respective lesion. Unquestionably required for lesion identification, internal structure becomes an essential radiographic aspect to differentiate the characteristic of a lesion. Several specific attributes of internal structure are utilized to distinguish each diagnosis. Thus, it is necessary to conduct specific assessment to discover the features of internal structure. Objective: To identify different radiographic features of internal structure in jaw lesions. Discussion: This article scrutinizes the internal structure of jaw lesions such as Pattern of Bones Destruction and Septation in Bone Lesions from several article reviews. A number of variances exist in the features of internal structure which later separate them from other lesions. The identification of cyst, benign and malignant tumor lesions may eventually be performed by using specific radiographic features of the lesions. Conclusion: Radiographic features of internal structure in jaw lesions illustrate particular hallmarks and traits which assist the identification of a lesion.